2017
DOI: 10.1111/mve.12281
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide susceptibility status in Mexican populations of Stegomyia aegypti (= Aedes aegypti): a nationwide assessment

Abstract: In Mexico, mosquito vector-borne diseases are of public health concern as a result of their impact on human morbidity and mortality. The use of insecticides against adult mosquitoes is one of the most common ways of controlling mosquito population densities. However, the use of these compounds has resulted in the development of insecticide resistance. The aim of this study was to estimate susceptibility to six pyrethroids, two carbamates and two organophosphates in Mexican populations of Stegomyia aegypti (Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
0
23
0
3
Order By: Relevance
“…The heavy reliance on pyrethroid insecticides for mosquito control has led to widespread pyrethroid resistance on a global scale [72]. The high levels of resistance to pyrethroids found in Mexico [73], including the Yucatan [49], prompted CENAPRECE to expand the chemical groups used for Aedes control to other insecticide classes such as carbamates and organophosphates, to which local Ae. aegypti are susceptible [49,73].…”
Section: Discussionmentioning
confidence: 99%
“…The heavy reliance on pyrethroid insecticides for mosquito control has led to widespread pyrethroid resistance on a global scale [72]. The high levels of resistance to pyrethroids found in Mexico [73], including the Yucatan [49], prompted CENAPRECE to expand the chemical groups used for Aedes control to other insecticide classes such as carbamates and organophosphates, to which local Ae. aegypti are susceptible [49,73].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that both products, one containing an organophosphate and the other containing a neonicotinoid-pyrethroid combination, proved to be effective at killing both the susceptible and local pyrethroid-resistant strain of Ae. aegypti (Correa-Morales et al 2016, Kuri-Morales et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Recent insecticide susceptibility tests have shown complete susceptibility of Ae. aegypti from Puerto Vallarta to chlorpyrifos in the state of Jalisco (CENAPRECE 2016, Correa-Morales et al 2016, Kuri-Morales et al 2017. To date, there are no broadly accepted diagnostic doses for prallethrin or imidacloprid to test for susceptibility of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Only Mexico and Colombia have a consistent insecticide resistance monitoring program, with only Mexico reporting a nationwide study on Ae. aegypti insecticide susceptibility status in recent years (44).…”
Section: Introductionmentioning
confidence: 99%